Down‐regulation of acid sphingomyelinase and neutral sphingomyelinase‐2 inversely determines the cellular resistance to plasmalemmal injury by pore‐forming toxins. Issue 1 (6th July 2018) - Schoenauer, Roman; Larpin, Yu; Babiychuk, Eduard B.; Drücker, Patrick; Babiychuk, Viktoriia S.; Avota, Elita; Schneider-Schaulies, Sibylle; Schumacher, Fabian; Kleuser, Burkhard; Köffel, René; Draeger, Annette
ABSTRACT: Bacterial pore‐forming toxins compromise plasmalemmal integrity, leading to Ca 2+ influx, leakage of the cytoplasm, and cell death. Such lesions can be repaired by microvesicular shedding or by the endocytic uptake of the injured membrane sites. Cells have at their disposal an entire toolbox of repair proteins for the identification and elimination of membrane lesions. Sphingomyelinases catalyze the breakdown of sphingomyelin into ceramide and phosphocholine. Sphingomyelin is predominantly localized in the outer leaflet, where it is hydrolyzed by acid sphingomyelinase (ASM) after lysosomal fusion with the plasma membrane. The magnesium‐dependent neutral sphingomyelinase (NSM)‐2 is found at the inner leaflet of the plasmalemma. Because either sphingomyelinase has been ascribed a role in the cellular stress response, we investigated their role in plasma membrane repair and cellular survival after treatment with the pore‐forming toxins listeriolysin O (LLO) or pneumolysin (PLY). Jurkat T cells, in which ASM or NSM‐2 was down‐regulated [ASM knockdown (KD) or NSM‐2 KD cells], showed inverse reactions to toxin‐induced membrane damage: ASM KD cells displayed reduced toxin resistance, decreased viability, and defects in membrane repair. In contrast, the down‐regulation of NSM‐2 led to an increase in viability and enhanced plasmalemmal repair. Yet, in addition to the increased plasmalemmal repair, the enhanced toxin resistance of NSM‐2 KD cells also appeared to be dependent on the activation of p38/MAPK, which was constitutively activated, whereas in ASM KD cells, the p38/MAPK activation was constitutively blunted.—Schoenauer, R., Larpin, Y., Babiychuk, E. B., Drücker, P., Babiychuk, V. S., Avota, E., Schneider‐Schaulies, S., Schumacher, F., Kleuser, B., Köffel, R., Draeger, A. Down‐regulation of acid sphingomyelinase and neutral sphingomyelinase‐2 inversely determines the cellular resistance to plasmalemmal injury by pore‐forming toxins. FASEB J. 33, 275–285 (2019). www.fasebj.org